THE DEVELOPMENT OF NEUTROPHILIC POLYMORPHONUCLEAR LEUKOCYTES IN HUMAN BONE MARROW : ORIGIN AND CONTENT OF AZUROPHIL AND SPECIFIC GRANULES - Bainton, Dorothy Ford (The Rockefeller University Press, 1971)
Neutrophilic leukocytes (PMN) and their precursors from normal human marrow and blood were examined by histochemical staining and by electron microscopy and cytochemistry in order to determine the origin and nature of their cytoplasmic granules. Human neutrophils contain two basic types of granules, azurophils and specifics, which differ in morphology, contents, and time of origin. Azurophils are large and may be spherical or ellipsoid, the latter with a crystalline inclusion. They are produced in the first secretory stage (promyelocyte), contain peroxidase and various lysosomal enzymes, and thus correspond to modified primary lysosomes. Specifics are smaller, may be spherical or elongated, and are formed during a later secretory stage (myelocyte). They lack lysosomal enzymes and contain alkaline phosphatase and basic protein; their contents remain largely undetermined. Specifics outnumber azurophils in the mature PMN because of reduction in numbers of azurophils per cell by cell division in the myelocyte stage. The findings indicate that the situation is basically the same as described previously in the rabbit, insofar as the origin, enzymic activity, and persistence in the mature cell of the two types (azurophil and specific) of granules are concerned. The main difference between PMN of the two species is in the morphology (size, shape, and density) of the granules, especially the azurophils.